Design and Investigation of Alginate Coated Solid Lipid Nanoparticles for Oral Insulin Delivery - Koland, Marina; Anchan, Rakshitha Bhaskar; Mukund, Sawan Ghetia; Mulleria, Sindhoor Shridharan (Indian Journal of Pharmaceutical Education and Research, 2021)
Introduction: The conventional subcutaneous administration of insulin has been associated with several limitations leading to poor patient compliance. The poor oral bioavailability of insulin due to degradation by gastrointestinal enzymes and secretions can be countered by the use of protective carriers such as solid lipid nanoparticles that are capable of being taken up by the Peyer’s patches. The aim of the investigation was to design and investigate alginate coated solid lipid nanoparticles (SLN) of insulin for oral administration. Materials and Methods: The SLN were prepared from glyceryl behenate and glyceryl monostearate and coated with mucoadhesive polymer, sodium alginate. The SLN were evaluated for size, shape, zeta potential, drug content, in vitro release and ex vivo drug permeation through goat intestinal mucosa and Caco-2 cell monolayer model. Results and Discussion: Transmission electron microscopy revealed spherical particles of uniform size distribution. In vitro drug release using the reverse dialysis method revealed that the alginate coating maintained the potency of insulin in simulated GI fluids and also provided sustained release. Absorption enhancement was demonstrated in ex vivo permeation studies in the goat intestinal mucosal model as well as in the Caco-2 cell monolayer model. The oral administration of alginate-coated insulin SLN in streptozotocin induced diabetic rats resulted in a significant hypoglycemic effect as compared to that of uncoated insulin-loaded SLN. The percentage glycemia at the end of 10 h was statistically significant (p<0.05) to oral insulin and the hypoglycemic levels reached were comparable to that of the conventional subcutaneous insulin. Conclusion: Alginate coated SLN has the potential of improving the absorption of insulin through intestinal mucosa and possibly its bioavailability.
Keywords: Solid lipid nanoparticle; Insulin; Oral delivery; Sodium alginate; Glycerol; monostearate; Hypoglycemia